Effect of dry needling on the variability of cardiac frequency in university members with temporomandibular dysfunction (Research, Society and Development, 2021)
Introduction: Despite the existence of some theories about the effect of Dry Needling on pain, there is still a lack of research using this technique in the treatment of temporomandibular disorder and its repercussions on the autonomic nervous system. Therefore, the aim was to analyze the effect of Dry Needling on the autonomic modulation of university students with temporomandibular disorders. Methods: This is an interventional, inferential study, carried out with university students with temporomandibular disorders. A frequency meter was used before, during, and after the application of the dry needle to verify its short and medium term effect on the autonomic nervous system. For statistical analysis, the ANOVA test was used. Results: Twenty volunteers with an average age of 21.3 years took part in the study, most of them male (65%). When the rMSSD and pNN50 indexes were analyzed, an increase was observed during dry needling (p = 0.701 and 0.452, respectively). However, after application, these indices fell, remaining above the base values. However, the triangular RR and TINN indices showed a constant increase during collection (p = 0.578 and 0.613, respectively). The high frequency component increased during the technique (p = 0.860), but the same did not happen with the low frequency component (p = 0.693), which suffered a constant increase, even with minor variation. Conclusion: The effect of this technique promotes the improvement of the heart rate variability values, maintaining the balance of the autonomic nervous system without generating cardiovascular risks, and its effects were immediate and lasting.